The knowledge of Nursing students related to pressure injury in bedridden patients (Research, Society and Development, 2020)
Pressure injury is a very common phenomenon, presenting a high worldwide prevalence with the need for evaluative measures for this type of injury. The aim of the study is to describe the knowledge of nursing students at a university center about pressure injuries; identify the profile of the nursing students in the study; discuss the knowledge of nursing students based on the existing framework on pressure injuries. This is a descriptive, exploratory study with a qualitative approach that will be carried out in a university center in the south of the city of Teresina-PI. The study will be conducted with 20 nursing students, from the fifth period of the morning and afternoon who have already seen the subject addressed. They will be interviewed by means of a semi-structured interview script signed by the Informed consent form. Exclusion criteria will be academic for periods shorter than the fifth. After conducting the data collection, they will be analyzed using Minayo's content analysis technique. The study showed the speeches of the academics who summarized the knowledge related to pressure injuries, with speeches that showed about: concept, cause, classification, prevention and treatment. With the completion of the study, it was possible to achieve the objectives, allowing to identify that nursing students still have some difficulties in the description of the pressure injury, but that they have some important knowledge on the subject.